Healing sanctuaries: between science and religion - Ozarowska, L (2016)
Divine healing has been often seen in opposition to human healing. The two spheres, have been considered as separate, both in space and in terms of elements involved. Asclepian sanctuaries have been mostly presented as domains of exclusively divine intervention, without any involvement of the human factor, possibly with the sole exception of dream interpretation. However, the written testimonies of temple cures, both those in the form of cure inscriptions dedicated in sanctuaries and the literary accounts of the incubation experience, give us reasons to suppose that the practical side of the functioning of the asklepieia could have assumed the involvement of human medicine, with the extent of this involvement differing in various epochs. Regardless of physicians’ participation or its lack in the procedure, the methods applied in sanctuary healing appear to have evolved in parallel to the developments in medicine and their popular perception. Archaeological finds as well as the image of Asclepius as the god of medicine itself seem to confirm this. Nevertheless, by no means should these connections between the two spheres be treated as transforming the space of religious meaning into hospitals functioning under the auspices of a powerful god. Although acknowledging them does entail inclusion of human medicine within the space dedicated to Asclepius, it does not thereby deny the procedure of incubation its religious and metaphysical dimension. On the contrary, it shows that to the Greek mind divine and human healing were not mutually exclusive, but overlapped and coincided with each other, proving that the Greek sense of rationality was quite different from the modern and could comprise far more than what we call today "scientific thinking".